Generation of megahertz-band spin currents using nonlinear spin pumping - Shingo Watanabe (Nature Portfolio, 2017)
Abstract Spin pumping enables the generation of d.c. and gigahertz-band (GHz-band) voltages from an applied microwave via magnetization dynamics when combined with inverse spin Hall effects. However, generating such voltages in the in-between frequency region, or the megahertz (MHz) band, has been difficult since ferromagnetic resonance usually occurs in the GHz band. Here we show that in spite of GHz-band microwaves applied, MHz-band voltages can be generated by spin pumping with use of nonlinear magnetization dynamics in Y3Fe5O12. The mechanism is ascribed to the MHz-band oscillation of the amplitude of the magnetization precession, which is projected onto a rectified voltage component via spin pumping. The present finding could be useful for frequency down-conversion thanks to the simple and durable structure, continuous-wave operation, and the tunability of an output frequency with low magnetic fields.